Aplikasi User Interface Berbasis Android pada Perpustakaan Lafran Pane Tapanuli Selatan Menggunakan Customer Relationship Management - Siregar, Umi Kalsum; Ikhwan, Ali (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The Lafran Pane Library is a library located in Pangurabaan village, Sipirok Tapanuli Selatan.  With today's technological developments This allows the library to be less developed because the library still uses a manual system and does not attract the attention of visitors. Apart from that, visitors who only want to borrow books must go to the library directly and must produce a membership card to be able to borrow books, so it wastes a lot of time. To overcome this problem, it is necessary to build an Android-based user interface information system. This application is designed for Android based on Customer Relationship Management (CRM), The concept of CRM is very relevant to library information services and helping libraries provide information services that satisfy users and build loyal user communities. Android-based User Interface application at the Lafran Pane Library in Tapanuli Selatan, will result in an application that functions as a responsive and intuitive user interface. This application allows library members to easily access book catalogs, borrow and return books online, and get the latest information about library events and activities.